PEMETAAN KEBUTUHAN GURU GEOGRAFI TINGKAT SMA DI KABUPATEN WAY KANAN TAHUN 2013 - Akhmad Zulfikar Kurniawan; Buchori Asyik; Dedy Miswar (JPG (Jurnal Penelitian Geografi), 2014)
This study aims to map the distribution of geography teacher needs in Way Kanan district on 2013, to describe the distribution of geography teacher needs in the Way Kanan district Lampung Province in 2013, to get on information about the educational background of geography teacher in every school in the Way Kanan district on 2013, the Way Kanan distribution geography teacher corresponding to the amount needed in the Way Kanan District 2013. This study used a descriptive method. The objects of research are throughout the high school in the Way Kanan district that are 32 schools and have 29 geography teacher. Data was collected by using questionnaires and documentation. From the results, it can be stated that the distribution of high school geography teacher in the Way Kanan district Lampung Provincein 2013 was uneven and not suitable according to the number of teachers needed in every high school in the Way Kanan district in 2013.Penelitian ini bertujuan memetakan sebaran kebutuhan guru geogarfi di Kabupaten Way Kanan tahun 2013, mendeskripsikan sebaran kebutuhan guru geografi di Kabupaten Way Kanan Provinsi Lampung tahun 2013, mendapatkan informasi tentang latar belakang pendidikan guru geografi di setiap SMA di Kabupaten Way Kanan tahun 2013, dan sebaran guru geografi yang sesuai dengan jumlah yang dibutuhkan di Kabupaten Way Kanan tahun 2013. Penelitian ini menggunakan metode deskriptif. Objek penelitian seluruh SMA di Kabupaten Way Kanan yaitu berjumlah 32 sekolah dan memiliki 29 orang guru geografi. Pengumpulan data dilakukan dengan cara kuesioner dan dokumentasi. Dari hasil penelitian, dapat dinyatakan bahwa sebaran guru geografi SMA di Kabupaten Way Kanan Provinsi Lampung Tahun 2013 kurang merata dan tidak sesuai dengan jumlah guru yang dibutuhkan pada setiap SMA di Kabupaten Way Kanan tahun 2013.Kata kunci: kebutuhan guru, pemetaan, sebaran.